A Study of arbutin protective effect on cyclosporin A-induced oxidative damage - Fatemeh Khadir; Mahdi Pouramir; Gholamali Joorsaraie; Farideh Feizi; Hadi Sorkhi; Fatemeh Yousefi (Babol University of Medical Sciences, 2015)
Background: Cyclosporine A (CsA) is a potent immunosuppressant drug with therapeutic and toxic actions. The use of CsA is limited by its toxicity. Several researchers had proposed that oxidative stress could play an important role in CsA-induced toxicity. Arbutin has recently been shown to possess antioxidative and free radical scavenging abilities.The present study was designed to investigate the in vivo effects of arbutin on lipid peroxidation and antioxidant capacity in the serum of cyclosporine treated rats.  Methods: Adult male Wistar rats were divided into six groups (n=8/group): (I) control (no CsA and arbutin administration), (II and III) were treated subcutaneously (Sc) with arbutin (50,100 mg/kg/bw), respectively, (IV) administered CsA (25 mg/kg/bw) intraperitoneally (IP), (V and VI) received the combination of CsA (25 mg/kg/bw) i.p and arbutin (50,100 mg/kg/bw) Sc daily, respectively. At the end of the treatment (after3 weeks), serum lipid peroxidation was measured by thiobarbituric acid-reacting substances (TBARS) and serum total antioxidant capacity (ferric reducing ability of plasma [FRAP]) was assayed based on spectrophotometric method.  Results: TBARS had been significantly increased by CsA administration compared with control rats. Arbutin (50mg/kg/bw) completely prevented this effect, but arbutin (100 mg/kg/bw) alone or in combination with CsA significantly increased lipid peroxidation compared with controls.  Conclusion: Our data indicate that arbutin (50mg/kg/bw) had protective effect in the CsA-induced toxicity but high concentration of arbutin (100mg/kg/bw) showed meaningful oxidative and lipoperoxidative effects.